Molecular detection of Babesia infection in cattle in Yogyakarta, Indonesia - YUDHI RATNA NUGRAHENI; BAMBANG ARIYADI; ROCHMADIYANTO ROCHMADIYANTO; NINING KESUMANINGRUM; KUSWARI IMRAN; BAYU PRIYO KARTIKO; NUR ROHMI FARHANI; SUCI NURANI; ANA SAHARA; AAN AWALUDIN (Society for Indonesian Biodiversity, 2023)
Abstract. Nugraheni YR, Ariyadi B, Rochmadiyanto, Kesumaningrum N, Imran K, Kartiko BP, Farhani NR, Nurani S, Sahara A, Awaludin A. 2023. Molecular detection of Babesia infection in cattle in Yogyakarta, Indonesia. Biodiversitas 24: 4192-4198. Babesiosis is a tick-borne disease caused by hemoprotozoa that poses a significant threat to livestock production worldwide, including in Indonesia. This study aimed to assess the prevalence and molecular characterization of Babesia sp., the causative agent of babesiosis, in cattle from multiple regions in Central Java, Indonesia. The disease has had substantial negative economic impacts, highlighting the need for accurate prevalence data and effective disease control measures. A total of 13 blood samples were collected from cattle exhibiting symptoms of hematuria and babesiosis. The samples were obtained from smallholder farmers who reported these cases to local veterinarians in various regions of Yogyakarta, Indonesia. The farmers were selected based on their proximity to veterinary clinics and willingness to participate in the study. Upon sample collection, each blood sample was subjected to microscopic examination using Giemsa-stained blood smears. The examination aimed to identify the presence of Babesia parasites within the red blood cells. Positive samples, indicating the presence of Babesia infection, were further analyzed by molecular assay. Molecular tests were performed using Polymerase Chain Reaction (PCR) to detect the DNA of Babesia sp. Two specific genes were targeted: cytochrome b oxidase (cytb) and 18S small subunit ribosomal RNA (18S rRNA). PCR amplification was carried out following established protocols, and the resulting products were visualized using gel electrophoresis to confirm the presence of Babesia DNA. Statistical analysis was conducted to compare the sensitivity and efficacy of the two PCR methods (cytb and 18S rRNA). The data obtained from this study contributes to our understanding of the occurrence of babesiosis in Central Java's cattle population. The findings underscore the need for comprehensive babesiosis disease surveys to obtain accurate prevalence estimates and facilitate the development of effective disease control strategies. Moreover, the more sensitive amplification targeting the cytb gene holds promise for improved diagnostic and surveillance efforts. These insights are crucial for combating babesiosis and mitigating its economic impact on livestock production.